Pete the cat's train trip - Dean, James 1957- (I can read! My first shared reading, 2015)
Embarking on a train trip to visit his grandmother, Pete the Cat accompanies the conductor on a tour of the train, looks at the engine and blows the whistle while making new friends and playing train-themed games